2022
DOI: 10.52312/jdrs.2023.853
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-carnitine on healing of Achilles tendon in rats

Abstract: Objectives In this experimental study, we aimed to analyze the effects of levocarnitine (L-carnitine) on tendon healing after surgical repair of Achilles tendon rupture in a rat model. Materials and methods The study included 40 Wistar Albino rats divided into four groups: Group 1, neither surgical intervention nor substance applications were performed for the Achilles tendons. In the other groups, the right Achilles tendons were cut using a scalpel and repaired with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Contrary, significant differences were found between the groups in histopathological parameters of inflammation (p = 0.010), neovascularization (p = 0.005), and fibroblastic activity (p = 0.005) in our study. The reason of Kuşcu et al (27) results may be the short-period of application of LC. However, they did not determine LC detrimental effect on tendon healing.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Contrary, significant differences were found between the groups in histopathological parameters of inflammation (p = 0.010), neovascularization (p = 0.005), and fibroblastic activity (p = 0.005) in our study. The reason of Kuşcu et al (27) results may be the short-period of application of LC. However, they did not determine LC detrimental effect on tendon healing.…”
Section: Discussionmentioning
confidence: 97%
“…Kuşcu et al (27) investigated the effect of LC on experimental Achilles tendon repairment histopathologically. In this study, it was performed that control group was applied nothing, but after surgical repair of the Achilles tendon, the sham group was given to nothing, the serum physiologic (SF) group was given one week SF, and LC group was given intraperitoneally for one week.…”
Section: Discussionmentioning
confidence: 99%
“…This complex mechanism is essential for fundamental activities such as walking, jumping, and running. [ 1 , 2 ] Notably, the incidence of acute tendon injuries tends to rise within the age range of 30 to 40 years, predominantly affecting male individuals. These injuries are frequently linked to recreational sports, such as ball games and racket sports, that involve rapid acceleration and jumping.…”
Section: Introductionmentioning
confidence: 99%
“…[1] For full-thickness tears of the Achilles tendon, which is the most common injury site of the lower extremity, recent studies have reported comparable results of conservative treatment with accelerated rehabilitation in the early term with surgical treatment, while a debate on the subject continues. [2][3][4][5] By effectively minimizing complications, open surgical repair of Achilles tendon tears can yield positive functional results and low recurrence rates. [6] Nonetheless, wound Tendons, similar to several other tissue types, are poorly vascularized, hypocellular, and heal slowly.…”
mentioning
confidence: 99%